Catalogue of the Cerambycidae (Coleoptera) of the Neotropical Region. Part II. Subfamily Lamiinae - Monné, Miguel A. (Zootaxa, 2005)
A catalogue of the subfamily Lamiinae (Coleoptera: Cerambycidae) of the Neotropical region is presented. The tribes (36), genera (723), species (4231) and subspecies (60) are listed in alphabetical order. Under each family-group name bibliographical references are given and under each species-group name, data on the type-locality, the acronym of the institution where the type is deposited, the geographical distribution and detailed bibliographical references are provided. Two new combinations are proposed: Urographis eucharis (Bates, 1885), new comb. and Urographis vexillaris (Bates, 1872) new comb., both from Graphisurus LeConte, 1852, not Kirby, 1837. The following new names are given: Alcathousiella new name to replace Alcathous Thomson, 1864, preoccupied by Alcathous Stal, 1863, Hemiptera; Camposiellina new name to replace Camposiella Lane, 1972, preoccupied by Camposiella Hebard, 1924, Orthoptera; Edechthistatus new name to replace Parechthistatus Giesbert, 2001, preoccupied by Parechthistatus Breuning, 1942, Coleoptera; Elytracanthina new name to replace Elytracantha Lane, 1955, preoccupied by Elytracantha Kleine, 1915, Coleoptera; Eranina new name to replace Erana Bates, 1866, preoccupied by Erana Gray, 1840, Aves; Heteresmia new name to replace Esmia Pascoe, 1859, preoccupied by Esmia Leach, 1847, Mollusca; Eupalessa new name to replace Eupales Dillon & Dillon, 1945, preoccupied by Eupales Lefevre, 1885, Coleoptera; Melzerus new name to replace Idiomerus Melzer, 1934, preoccupied by Idiomerus Imms, 1912, Collembola; Midamiella new name to replace Midamus Dillon & Dillon, 1945, preoccupied by Midamus Simon, 1881, Arachnida; Neoamphion new name to replace Amphion Reiche, 1840, preoccupied by Amphion Huebner, 1819, Lepidoptera; Neocolobura new name to replace Colobura Blanchard, 1851, preoccupied by Colobura Billberg, 1820, Lepidoptera; Neohoplonotus new name to replace Hoplonotus Blanchard, 1851, preoccupied by Hoplonotus Schmidt-Goebel, 1846, Coleoptera; Neohylus new name to replace Hylus Dillon & Dillon, 1945, preocuppied by Hylus Van Dyke, 1945, Coleoptera; Neolampedusa new name to replace Lampedusa Dillon & Dillon, 1945, preoccupied by Lampedusa Boettger, 1877, Mollusca; Proseriphus new name to replace Seriphus Bates, 1864, preoccupied by Seriphus Ayres, 1857, Pisces. One new synonym is proposed: Proxepectasis Monné & Giesbert, 1992 = Parepectasoides Breuning, 1979.